Pengembangan Manajemen Sumber Daya Manusia pada Lembaga Pendidikan Islam - Junaidi Junaidi; Zalisman Zalisman; Yusnimar Yusri; Khairul Amin; Wismanto Wismanto (Departement of Mathematics Education, 2023)
Quality Human Resources is the biggest capital and the most important thing to pay attention to. Human Resources must continue to be developed so that they can always keep up with the times. Advances in science and technology require everyone involved in the circle of educational institutions to be ready to transform for the advancement of the institution and the human person. To examine more deeply, this research was conducted using library research methods (library research). Library research is a series of activities to collect library data by reading, recording, and interpreting into research data. This library method is also research by making literature as the main data source. The development of human resources in educational institutions should involve all elements involved in their organization, from school principals, teachers, education staff to school security. The process of developing human resources in educational institutions must also be based on needs analysis and careful planning so that they can support the process of achieving educational institution goals. A good and careful process will produce human resources, namely qualified teaching and educational staff.